New epidemiological aspects of visceral and cutaneous leishmaniasis in Taza, Morocco. Issue 1 (December 2016) - Hakkour, Maryam; Hmamouch, Asmae; Alem, Mohamed; Rhalem, Abdelkbir; Amarir, Fatima; Touzani, Mohamed; Sadak, Abderrahim; Fellah, Hajiba; Sebti, Faiza
Abstract Background Leishmaniasis is considered among the main endemic diseases in Morocco. However, further knowledge about epidemiological aspects of this disease is needed in several provinces to plan control and preventive strategies to tackle the disease. The present study aims to determine the epidemiological aspect of cutaneous and visceral leishmaniasis in Taza Province from 2007–2014 and to identify the circulating species in this province. Results The temporal study from 2007 to 2014 showed that the number of cutaneous leishmaniasis cases increased since 2010. During the period of study, most leishmaniasis cases were detected in both urban and rural areas with 34% of cases detected in two urban localities, Bab Zitouna and Bab tété with 297 and 106 cases, respectively. The molecular study of cutaneous leishmaniasis showed the presence of non-sporadicLeishmania infantum andLeishmania tropica in this province. Regarding visceral leishmaniasis, Leishmania infantum is the species that has been identified. Conclusions The epidemio-molecular study of leishmaniasis in Taza Province showed the coexistence of two species ofLeishmania in the same foci. They also indicated that CL due toLeishmania infantum is more prevalent than reported in the literature. These results will be helpful for the implementation of control strategies by targeting dogs that constitute a reservoir ofLeishmania infantum .